2023
DOI: 10.3390/app13031524
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacterial Communities Associated with Solitary Bee Osmia excavata Alfken (Hymenoptera: Megachilidae)

Abstract: Insect-associated microorganisms play important roles in the health and development of insects. This study aimed to investigate the similarities and differences in bacterial community structure and composition between the larval gut of Osmia excavata, nest soil, and brood provision from the nest tube. We sequenced larvae gut and their environments’ microorganisms of O. excavata from four locations based on full-length 16S rRNA gene amplicons. The results showed 156, 280, and 366 bacterial OTUs from gut, brood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The results of our previous study have shown that the freezing point and supercooling point of O. excavata are both approximately −10 °C (Liu et al. , 2018b); hence, we suggest that the long‐term refrigeration at 0 °C in this study did not interfere with the water balance or induce physiological harm. In recent years, antifreeze proteins, such as heat‐shock proteins, ice nucleator proteins, and lipoproteins, have been identified in many insects; these proteins allow insects to survive in low‐temperature environments (Ouyang & Ge, 2014).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results of our previous study have shown that the freezing point and supercooling point of O. excavata are both approximately −10 °C (Liu et al. , 2018b); hence, we suggest that the long‐term refrigeration at 0 °C in this study did not interfere with the water balance or induce physiological harm. In recent years, antifreeze proteins, such as heat‐shock proteins, ice nucleator proteins, and lipoproteins, have been identified in many insects; these proteins allow insects to survive in low‐temperature environments (Ouyang & Ge, 2014).…”
Section: Discussionsupporting
confidence: 52%
“…and reduce the rate of development of Apis mellifera (Zhu et al, 2015;Liu et al, 2021). In recent years, Osmia populations, along with their pollination services, have severely declined, and unsuitable growing conditions are considered the main cause of this decline (Cao et al, 2017;Liu et al, 2018a;Song et al, 2021). However, few studies have investigated the effects of cold storage on Osmia, especially in mature or overwintered bees (Bennett et al, 2013;Campoy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the halictid bees Halictus ligatus and Lasioglossum pilosum, Sodalis was absent when Lactobacillus dominated the microbiome at 94% and 9%, respectively (54). Similar trend was also seen in Osmia excavate, where dominance of Sodalis decreased the abundance of A. micheneri and vice-versa (55). In Hymenopterans, Sodalis is maternally inherited and can potentially compromise reproductive compatibility (56).…”
Section: Discussionmentioning
confidence: 93%
“…Honeybee foragers collect and bring the pollen to the hive (bee-pollen), where it is mixed with glandular secretions, nectar, or honey, processed by symbiont microbes, and becomes bee bread, the naturally fermented pollen that is colonies’ staple food [ 34 ]. Bee bread is a highly nutritious food that contains large bacterial diversity, some of which is crucial for the performance of the fermentation process conducting transformation of pollen (plant material) into a more digestible form for bees, and further contributing not only to their nutritional needs, but providing bioactive metabolites clearly associated with overall hive health, including protection against harmful microbes and contributes to the detoxification processes [ 34 , 35 ]. Different bacterial genera are observed in bee bread, with variation in the relative abundance of dominant taxa in the different layers of the product and types of ecosystems [ 30 ].…”
Section: The Microbiota Of Western Honeybees ( Apis Mellife...mentioning
confidence: 99%
“…For solitary bees ( Osmia excavate ), the specificity of bacterial community architecture and diversity associated with the gut of larva, characteristics of the nest soil, and brood provision from the nest tube, are factors investigated and pointed to as crucial for the observed significant differences in microbial diversity between brood provision groups and nest soil groups [ 35 ]. Reported observations emphasize the complexity of the microbiota of solitary bees and the relevance of the potential impact that the microbial community of solitary bees can play on their health and physiology [ 35 , 47 ].…”
Section: Other Bee Species Microbiotamentioning
confidence: 99%